Il senso della morte in adolescenza: scoperta della caducità umana e risposta pedagogica - Maria Rita Mancaniello (Firenze University Press, 2019)
Within adolescence transformation the encounter with the sense of death is crucial, despite is not highlighted in pedagogical and educational reflection. The adolescent deep metamorphosis, considering physical, psychological, social and relational change determined by puberty beginning, lead the subject to know sensations and emotions that have mourning characteristics, and more precisely self mourning, meaning all cognitive and emotional experiences that loss brings. A dimension of being and becoming that has to be necessarily considered by those who reflect on education and those who assist adolescents in their growing process. Accompanying, in an educational way, the adolescent subject on the discovery of death meaning allows to avoid individual and collective removals, which is one of the most tragical aspects of contemporary life, and allows a positive relapse compared to self relationship and with own social dimension.